Evaluasi Pencapaian Kartu Kredit Syariah di Era Konvensional - Septi Widya Sari; Vivi Silvia (Jurnal Ekonomi dan Bisnis Digital, 2023)
This article is entitled evaluation of the achievements of sharia credit cards in the conventional era, is motivated by seeing the intense competition between conventional and sharia systems in Indonesia. As time goes by, many banking companies are competing to create facilities with the aim of making it easier and more interesting for consumers to make any transactions. One of the facilities the author discusses here is a credit card product. Increasing activity, especially in terms of business, credit cards certainly make it easier for people to make transactions. However, credit cards must comply with Islamic principles and must not deviate from the provisions of Islamic credit law.